2019
DOI: 10.3390/ijerph17010077
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Expectations and Factors Influencing Exclusive Breastfeeding during the First 6 Months

Abstract: The aims were to determine Spanish women’s expectations about exclusive breastfeeding (EB) and the effect of expectations and other factors on EB during the first 6 months. A prospective cohort study was conducted with 236 participants. Variables were maternal age, marital status, occupation, expectations about breastfeeding, knowledge about breastfeeding, type of delivery, type of feeding, and duration of EB. Data were collected through three personal interviews, at the hospital (before delivery) and in two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
4
33
0
2
Order By: Relevance
“…The average age of the study population was 32.16 years, which is in line with the average maternal age in Spain (32.20 years, Spanish Statistics Institute) [ 35 ] and Andalusia (31.68 years) [ 35 ] recorded for the study year 2017. The average duration of breastfeeding was 111.48 days, with an SD of 68.449 days (0–180), which is in agreement with that reported in other studies [ 11 , 12 ]. The evolution of breastfeeding throughout the first six months after birth coincides with the descending trend observed at the Andalusian and Spanish level.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The average age of the study population was 32.16 years, which is in line with the average maternal age in Spain (32.20 years, Spanish Statistics Institute) [ 35 ] and Andalusia (31.68 years) [ 35 ] recorded for the study year 2017. The average duration of breastfeeding was 111.48 days, with an SD of 68.449 days (0–180), which is in agreement with that reported in other studies [ 11 , 12 ]. The evolution of breastfeeding throughout the first six months after birth coincides with the descending trend observed at the Andalusian and Spanish level.…”
Section: Discussionsupporting
confidence: 91%
“…Other authors have separately analysed spontaneous and induced birth; in this sense, Martínez-Galiano [ 13 ] observed that, in induced birth, the risk of abandonment was 5.6 times greater than in spontaneous births (OR: 5.6, CI95%: 1.107–28.322) [ 13 ]. According to Santacruz-Salas et al [ 11 ], in women who had a caesarean section, breastfeeding failure was 4.6 times greater than in those who had a vaginal birth (OR: 4.6, CI95%: 1.7–12.8) [ 11 ], which is in line with the results reported by other authors, such as Fernández-Cañadas [ 14 ], Brown and Jordan [ 15 ] and Carlander et al [ 16 ]. Other authors have separately studied urgent and programmed caesarean births; with the latter being the one with greater risk of interruption of exclusively breastfeeding with respect to urgent caesarean births [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations